Single molecule localizations of voltage-gated sodium channel NaV1.5 on the surfaces of normal and cancer breast cells. Issue 15 (24th March 2023) - Li, Xinyu; Zhao, Li; Feng, Rongrong; Du, Xiaowei; Guo, Zelin; Meng, Yu; Zou, Yulan; Liao, Wenchao; Liu, Qiyuan; Sheng, Yaohuan; Zhao, Gaowei; Zhong, Haijian; et al.
Abstract : The NaV 1.5 on cellular membranes of normal and cancer breast cells can be localized at single molecule spatial resolution level, and the interactions between the NaV 1.5 and antibody can be detected at picoNewton force resolution level. Abstract : Voltage-gated sodium channels (VGSCs) are widely expressed in various types of tumor and cancer cells, and NaV 1.5 is overexpressed in highly metastatic breast cancer cells. There may be positive relations between the expression levels of NaV 1.5 and breast cancer recurrence and metastasis. Herein, NaV 1.5 was detected and localized on the surfaces of normal and cancer breast cells by the single molecule recognition imaging (SMRI) mode of atomic force microscopy (AFM). The results reveal that NaV 1.5 was irregularly distributed on the surfaces of normal and cancer breast cells. The NaV 1.5 has an area percentage of 0.6% and 7.2% on normal and cancer breast cells, respectively, which indicates that there is more NaV 1.5 on cancer cells than on normal cells. The specific interaction forces and binding kinetics in the NaV 1.5–antibody complex system were investigated with the single molecule force spectroscopy (SMFS) mode of AFM, indicating that the stability of the NaV 1.5–antibody on normal breast cells is higher than that on cancer breast cells. All these results will be useful to study the interactions of other ion channel–antibody systems, and will also be useful to understand the role of sodium channels in tumor metastasis and invasion.